Determinants of Teacher Performance at State Senior High School 1 Plupuh Sragen Regency - Joko Susilo; Sudarwati; Istatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to see the effect of commitment, organizational culture, supervision and training on the performance of educators. The research design is a survey research. This research was conducted at SMA Negeri 1 Plupuh, which is located on the Sambirejo - Plupuh Sragen highway in June-August 2024. The object of the research was educators of SMA Negeri 1 Plupuh totaling 40 educators in the 2023/2024 academic year. The population of this study was all educators who taught at SMA Negeri 1 Plupuh totaling 40 educators. The sample taken in this study was all educators of SMA Negeri 1 Plupuh, so the sampling technique used was the saturated sampling technique. The variables in this study consisted of the independent variables used in this study are commitment, organizational culture, supervision and training. The dependent variable used in this study is educator performance. These variables were then processed using multiple regression analysis tools using SPSS 25 software. The results of the study concluded that commitment, organizational culture, supervision, and training contributed to educator performance. performance of educators at SMA Negeri 1 Plupuh.Based on the calculation results, the adjusted R square value was obtained as 0.937. This means that the variables of commitment, organizational culture, supervision, and training contributed to the performance of educators by 93.7%, while the remaining 6.3% was explained by other variables not proposed in this study. Keywords:commitment, organizational culture, supervision and performance of teaching and training staff